Product Modularization Considering Cost and Manufacturability of Modules - Nepal, Bimal; Monplaisir, Leslie; Singh, Nanua; Yaprak, Attila (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
It is argued that modular architecture allows us to create large product variety at lower cost, and in a shorter development cycle time. While it has been widely recognized that modular design improves assemblability, the manufacturability of modules themselves have rarely been considered during modularization. This paper presents a formal and integrated framework for product modularization by optimizing manufacturability of modules and costs of modularization during the earlier stages of product development. A fuzzy logic approach is used to handle the vague and imprecise product information available during the concept development phase of product development. The framework also facilitates sensitivity analysis to provide design engineers and managers with deeper insights on tradeoffs among conflicting design objectives. The methodology is validated through a case study on the modularization of an automotive climate control system.